Epidemiology of Navicular Injury at the NFL Combine and Their Impact on an Athlete's Prospective NFL Career. Issue 8 (17th August 2017) - Vopat, Bryan; Beaulieu-Jones, Brendin R.; Waryasz, Gregory; McHale, Kevin J.; Sanchez, George; Logan, Catherine A.; Whalen, James M.; DiGiovanni, Christopher W.; Provencher, Matthew T.
Background: Navicular injuries can result in persistent pain, posttraumatic osteoarthritis, and diminished performance and function. Purpose: To determine the epidemiology of navicular fracture in players participating in the National Football League (NFL) Scouting Combine and evaluate the impact of a navicular injury on the NFL draft position and NFL game play compared with matched controls. Study Design: Cohort study; Level of evidence, 3. Methods: Data were collected on players who previously sustained a navicular injury and participated in the NFL Combine between 2009 and 2015. The epidemiology of navicular injury was determined through an evaluation of the number of injuries, surgeries, and collegiate games missed as well as the position played, a physical examination, the surgical technique, and imaging findings. Players with a previous navicular injury (2009-2013) were compared with a set of matched controls. NFL performance outcomes included the draft position, career length ≥2 years, and number of games played and started within the first 2 years. Results: Between 2009 and 2015, 14 of 2285 (0.6%) players were identified as having sustained a navicular injury. A total of 11 of 14 (79%) athletes had sustained an overt navicular fracture, while 3 of 14 (21%) were diagnosed with stress reactions on magnetic resonance imaging. Eight patients who sustained a navicular fracture underwent surgery. There was evidence of ipsilateral talonavicular arthritis in 75% of players with a navicular fracture versus only 60% in the uninjured foot (odds ratio, 1.3; P = .04). Fifty-seven percent of players with navicular injury (72.7% of fractures) were undrafted versus 30.9% in the control group ( P = .001). Overall, 28.6% of players with navicular fracture played ≥2 years in the NFL compared with 69.6% in the control group ( P = .02). Conclusion: A previous navicular fracture results in a greater risk of developing posttraumatic osteoarthritis. Although only a low prevalence of navicular injury in prospective NFL players was noted, players with these injuries had a greater probability of not being drafted and not competing in at least 2 NFL seasons when compared with matched controls without an injury history to the NFL Combine.